Accuracy, Efficiency, and Inappropriate Actions Using JumpSTART Triage in MCI Simulations. Issue 5 (1st September 2015) - Claudius, Ilene; Kaji, Amy H.; Santillanes, Genevieve; Cicero, Mark X.; Donofrio, J. Joelle; Gausche-Hill, Marianne; Srinivasan, Saranya; Chang, Todd P.
Abstract: Introduction: Using the pediatric version of the Simple Triage and Rapid Treatment (JumpSTART) algorithm for the triage of pediatric patients in a mass-casualty incident (MCI) requires assessing the results of each step and determining whether to move to the next appropriate action. Inappropriate application can lead to performance of unnecessary actions or failure to perform necessary actions. Hypothesis/Problem: To report overall accuracy and time required for triage, and to assess if the performance of unnecessary steps, or failure to perform required steps, in the triage algorithm was associated with inaccuracy of triage designation or increased time to reach a triage decision. Methods: Medical students participated in an MCI drill in which they triaged both live actors portraying patients and computer-based simulated patients to the four triage levels: minor, delayed, immediate, and expectant. Their performance was timed and compared to intended triage designations and a priori determined critical actions. Results: Thirty-three students completed 363 scenarios. The overall accuracy was 85.7% and overall mean time to assign a triage designation was 70.4 seconds, with decreasing times as triage acuity level decreased. In over one-half of cases, the student omitted at least one action and/or performed at least one action that was not required. Each unnecessary action increased time to triage by a mean of 8.4 seconds and each omitted action increased time to triage by a mean of 5.5 seconds. Discussion: Increasing triage level, performance of inappropriate actions, and omission of recommended actions were all associated with increasing time to perform triage. I Claudius, AH Kaji, G Santillanes, MX Cicero, JJ Donofrio, M Gausche-Hill, S Srinivasan, TP Chang .Accuracy, efficiency, and inappropriate actions using JumpSTART triage in MCI simulations .Prehosp Disaster Med .2015 ;30 (5 ):457 –460 .